Hot Melt Extruded Posaconazole-Based Amorphous Solid Dispersions-The Effect of Different Types of Polymers - Daniel Kramarczyk; Justyna Knapik-Kowalczuk; Mateusz Kurek; Witold Jamróz; Renata Jachowicz; Marian Paluch (MDPI AG, 2023)
Four model polymers, representing (i) amorphous homopolymers (Kollidon K30, K30), (ii) amorphous heteropolymers (Kollidon VA64, KVA), (iii) semi-crystalline homopolymers (Parteck MXP, PXP), and (iv) semi-crystalline heteropolymers (Kollicoat IR, KIR), were examined for their effectiveness in creating posaconazole-based amorphous solid dispersions (ASDs). Posaconazole (POS) is a triazole antifungal drug that has activity against Candida and Aspergillus species, belonging to class II of the biopharmaceutics classification system (BCS). This means that this active pharmaceutical ingredient (API) is characterized by solubility-limited bioavailability. Thus, one of the aims of its formulation as an ASD was to improve its aqueous solubility. Investigations were performed into how polymers affected the following characteristics: melting point depression of the API, miscibility and homogeneity with POS, improvement of the amorphous API's physical stability, melt viscosity (and associated with it, drug loading), extrudability, API content in the extrudate, long term physical stability of the amorphous POS in the binary drug-polymer system (in the form of the extrudate), solubility, and dissolution rate of hot melt extrusion (HME) systems. The obtained results led us to conclude that the physical stability of the POS-based system increases with the increasing amorphousness of the employed excipient. Copolymers, compared to homopolymers, display greater homogeneity of the investigated composition. However, the enhancement in aqueous solubility was significantly higher after utilizing the homopolymeric, compared to the copolymeric, excipients. Considering all of the investigated parameters, the most effective additive in the formation of a POS-based ASD is an amorphous homopolymer-K30.